Psychometric Evaluation of the Stakeholder Support Questionnaire for Integrated Primary Care: Evidence of a Multidimensional and Hierarchical Construct in Indonesia - Wiwin Wiarsih; Utami Rachmawati; Muhamad Jauhar; Megah Andriany; Endang Triyanto; Lita Heni Kusumawardani; Maula Mar'atus Solikhah; Umi Hani; Kinantika Nur Dewanti; M.Agung Akbar (An Idea Health Journal, 2026)
Background: Integrated primary care (IPC) is recognized as essential for strengthening health systems. However, Indonesia currently lacks a validated instrument to assess stakeholder support, which is a critical determinant of successful IPC implementation. This study evaluated the content validity, internal structure, and reliability of the newly developed Stakeholder Support Questionnaire for Integrated Primary Care (SSQ-IPC), grounded in Freeman’s Stakeholder Theory. Methods: A cross-sectional psychometric validation was conducted with 570 primary healthcare nurses recruited through stratified random sampling across Indonesia. The initial 18-item instrument, encompassing four constructs, underwent content validation by a panel of seven experts. Data analysis included calculating the Content Validity Index (CVI), conducting exploratory factor analysis (EFA), confirmatory factor analysis (CFA), and second-order CFA. Model fit was assessed using multiple fit indices, while construct validity and reliability were evaluated through factor loadings, Average Variance Extracted (AVE), Cronbach’s alpha, and McDonald’s omega. Results: EFA supported a four-factor structure. First-order CFA indicated acceptable model fit (CFI = 0.933, TLI = 0.921, SRMR = 0.037), with all factor loadings statistically significant (p<.001) and strong indicator reliability. Convergent validity was established with AVE values ranging from 0.650 to 0.869, and internal consistency was high across constructs (α= 0.877–0.978; ω = 0.884–0.973). Second-order CFA supported a hierarchical model, with all four constructs significantly loading onto a higher-order factor. Conclusion: The SSQ-IPC demonstrates strong evidence of validity and reliability, supporting its multidimensional and hierarchical structure. This instrument provides a robust tool for research and practice, facilitating.